microRNAs and mRNAs genes associated with the development of ischemic heart disease (Experimental biology, 2016)
There was studied the characteristics of interaction of microRNAs with mRNAs of genes, involved in the development of ischemic heart disease. There was identified the 268 binding sites for 2564 miRNA in mRNA of 187 genes, participating in the development of IHD. Among them, 52 arranged in CDS, 23 in 5´UTR and 193 are in 3´UTR. From the database of miRNAs, participating in the development if IHD, there are no miRNA have binding sites in mRNA of 187 genes. mRNA of 44 genes have only one binding site of miRNA. mRNA of ANGPTL2, C3 and IGFBP3 genes bind with miR-1272. miR-1285-5p has binding sites in FGF2 and MMP2 genes. The ΔG/ΔGm value, characterizing the interaction of miRNA with mRNA of stidied genes is equal to 90-95%. Only the interaction of miR-1273g-3p with mRNA of FCGR2A gene is associated with the ΔG/ΔGm value equal to 98%. The obtained data allow to recommend for diagnosis of IHD: associations of miR-1272 with ANGPTL2, C3 and IGFBP3 genes; association of miR-1285-5p with FGF2 and MMP2 genes. miR-3960 has multiple binding sites in mRNA of DAB2IP gene and could be used as a diagnostic marker of IHD. Over five miRNA binds with mRNA of IGF1, MTHFR, PLA2G7 genes. Over six miRNA binds with mRNA of AS3MT, F2RL3,IL6R, MLXIPL, PPP1R3B and TGFB1 genes. Over seven miRNA binds with mRNA of LDLR and NPC1L1 genes. The nine miRNA binds with mRNA of IL6R gene that indicates a strong dependence on the expression of these genes from miRNA. The expression of many genes is dependent on the unique miRNAs: miR-619-5р has 14 target genes; miR-5095 and miR-5096 have 10 target genes. The family of miR-1273a,c,d,e,f,g,h have 38 binding sites including 19 binding sites of miR-1273g-3p in mRNA of 17 genes. mRNA of genes of interleukins IL10, IL18, IL6R with high degree binds with a group of unique  miRNAs: miR-619-5р, miR-5095 and miR-5096. In mRNA of several genes presented binding sites with miR-619-5р, miR-5585-3p. mRNA of NOS1 gene contains binding sites for miR-619-5p, miR-5095, miR-1273g-3p, miR-574-5p and miR-466. miR-466 has multiple binding sites in ICAM1, TNFSF4, MLXIPL and PLA2G7 genes. miR-574-5p has multiple binding sites in IGF1 and PPARA genes. Some associations of miRNA with mRNA have a higher free energy of interaction (ΔG). miR-1273d consisting from 25 n. binds with mRNA of SMARCA4 gene with ΔG value equal to -125 kJ/mole, miR-762 consisting from 22 n. binds with mRNA of CSMD1 gene with ΔG value equal to -127 kJ/mole. miR-6789-5p consisting from 24 n. binds with mRNA of FADS3 and HIF1Agenes with ΔG value equal to -129 kJ/mole and 132 kJ/mole. miR-6089-5p consisting from 24 n. binds with mRNA of TGFB1gene in two binding sites with ΔG value equal to -132 kJ/mole and 136 kJ/mole. The same miRNA binds with mRNA of IL6R gene with ΔG value equal to -138 kJ/mole that makes 93% from maximum free energy of binding.
Keywords: miRNA; mRNA; binding sites; target genes; ischemic heart disease.